Causal effects of systemic inflammatory proteins on Guillain-Barre Syndrome: insights from genome-wide Mendelian randomization, single-cell RNA sequencing analysis, and network pharmacology - Liu, Jingwen; Pan, Renbing (Frontiers in Immunology, 2024)
Background Evidence from observational studies indicates that inflammatory proteins play a vital role in Guillain-Barre Syndrome (GBS). Nevertheless, it is unclear how circulating inflammatory proteins are causally associated with GBS. Herein, we conducted a two-sample Mendelian randomization (MR) analysis to systematically explore the causal links of genetically determined systemic inflammatory proteins on GBS. Methods A total of 8,293 participants of European ancestry were included in a genome-wide association study of 41 inflammatory proteins as instrumental variables. Five MR approaches, encompassing inverse-variance weighted, weighted median, MR-Egger, simple model, and weighted model were employed to explore the causal links between inflammatory proteins and GBS. MR-Egger regression was utilized to explore the pleiotropy. Cochran’s Q statistic was implemented to quantify the heterogeneity. Furthermore, we performed single-cell RNA sequencing analysis and predicted potential drug targets through molecular docking technology. Results By applying MR analysis, four inflammatory proteins causally associated with GBS were identified, encompassing IFN-γ (OR:1.96, 95%CI: 1.02-3.78, PIVW=0.045), IL-7 (OR:1.86, 95%CI: 1.07-3.23, PIVW=0.029), SCGF-β (OR:1.56, 95%CI: 1.11-2.19, PIVW=0.011), and Eotaxin (OR:1.99, 95%CI: 1.01-3.90, PIVW=0.046). The sensitivity analysis revealed no evidence of pleiotropy or heterogeneity. Additionally, significant genes were found through single-cell RNA sequencing analysis and several anti-inflammatory or neuroprotective small molecular compounds were identified by utilizing molecular docking technology. Conclusions Our MR analysis suggested that IFN-γ, IL-7, SCGF-β, and Eotaxin were causally linked to the occurrence and development of GBS. These findings elucidated potential causal associations and highlighted the significance of these inflammatory proteins in the pathogenesis and prospective therapeutic targets for GBS.